Risk factors of gastric premalignant lesion in gastritis patients - Siregar, Gontar Alamsyah; Parwati, Ida; Achmad, Tri Hanggono; Syukriani, Yoni Fuadah (Penerbit Universiti Kebangsaan Malaysia, 2018)
Gastric cancer is the second leading cause of cancer-related mortality and the fourth most common cancer globally. Gastric premalignant lesions are well known risk factors for the development of gastric cancer. The purpose of this study was to investigate the risk factors of gastric premalignant lesion. This cross-sectional study observed gastritis patients at Adam Malik General Hospital, Permata Bunda General Hospital, Universitas Sumatera Utara Hospital, all located in Medan, Indonesia. A total of 120 gastritis patients were included in this study. Patients were interviewed with a questionnaire to obtain demographic data, alcohol intake, smoking status, high salt diet and NSAID use. Diagnosis of Helicobacter pylori infection was made using positive results of the carbon-14 urea breath test (14C-UBT), rapid urease test, and/or immunohistochemistry. Endoscopy and biopsy were conducted to diagnose gastric premalignant lesion. Gastric premalignant lesion diagnosis was made when one or more of the following were present: Chronic atrophic gastritis, intestinal metaplasia, or dysplasia. Data were analysed using SPSS version 22. There were 35/120 (29.2%) of gastritis patients having gastric premalignant lesion. Multivariate analysis has shown that H. pylori infection, patients with family history of gastric cancer, alcohol consumption and Batak ethnic have increased risk to develop gastric premalignant lesion (p<0.05). All these results implied that risk factors of gastric premalignant lesion were H. pylori infection, family history of gastric cancer, alcohol intake and Batak ethnic.